Robotic transduodenal ampullectomy: A novel minimally invasive approach for ampullary neoplasms. Issue 3 (8th January 2019) - Lee, Jin Woo; Choi, Sung Hoon; Chon, Hong Jae; Kim, Dae Jung; Kim, Gwangil; Kwon, Chang Il; Ko, Kwang Hyun
Abstract: Background: The adoption of minimally invasive surgery for transduodenal ampullectomy has been slow because of special characteristics and complexity of this procedure. Methods: Six patients underwent robotic transduodenal ampullectomy. We employed novel methods to facilitate exposure of the ampulla. Results: All patients completed robotic transduodenal ampullectomy, but one patient was immediately converted to robotic pancreaticoduodenectomy because of presence of invasive carcinoma on frozen biopsy. The final pathologic report revealed high‐grade dysplasia in four patients, low‐grade dyplasia in one, and T2N0 in one patient who converted to pancreaticoduodenectomy. There was no immediate postoperative complication or mortality. One patient was readmitted after 3 months because of stricture of the bile duct outlet. There was no recurrence over a median follow‐up period of 20 months. Conclusion: An appropriate combination of patient positioning and retraction method helps the robot surgical system to provide competent performance for sophisticated and precise manipulation of ampullary lesions.